The Hippo/YAP pathway interacts with EGFR signaling and HPV oncoproteins to regulate cervical cancer progression - Chunbo He; Dagan Mao; Guohua Hua; Xiangmin Lv; Xingcheng Chen; Peter C Angeletti; Jixin Dong; Steven W Remmenga; Kerry J Rodabaugh; Jin Zhou; Paul F Lambert; Peixin Yang; et al. (EMBO Molecular Medicine)
Abstract The Hippo signaling pathway controls organ size and tumorigenesis through a kinase cascade that inactivates Yes‐associated protein (YAP). Here, we show that YAP plays a central role in controlling the progression of cervical cancer. Our results suggest that YAP expression is associated with a poor prognosis for cervical cancer. TGF‐α and amphiregulin (AREG), via EGFR, inhibit the Hippo signaling pathway and activate YAP to induce cervical cancer cell proliferation and migration. Activated YAP allows for up‐regulation of TGF‐α, AREG, and EGFR, forming a positive signaling loop to drive cervical cancer cell proliferation. HPV E6 protein, a major etiological molecule of cervical cancer, maintains high YAP protein levels in cervical cancer cells by preventing proteasome‐dependent YAP degradation to drive cervical cancer cell proliferation. Results from human cervical cancer genomic databases and an accepted transgenic mouse model strongly support the clinical relevance of the discovered feed‐forward signaling loop. Our study indicates that combined targeting of the Hippo and the ERBB signaling pathways represents a novel therapeutic strategy for prevention and treatment of cervical cancer.